Effectiveness of Combination Application of Grinting Grass (Cynodon Dactylon) Extract and Tumb of Gadung (Dioscorea Hispida Dennst) Plant as an Attempt to Suppress the Intensity of Mosaik Virus Vector Pest (Aphis Glycine) in Soybean (Glycine Max L.) Plants - Malik , Fahmi Faishal; Ikhwan, Ali; Septia, Erfan Dani (Universitas Muhammadiyah Malang, 2022)
A. glycine soybean infestation caused yield loss reaching 58%. Environmental friendly controls are carried out using natural ingredients. This study was conducted to determine the effectiveness of the combination of gadung and grass grinting tuber extracts on soybean virus (A. glycine) vector pests and to know the mechanism of toxicity to these pests. This research was conducted from June to September 2018. The effectiveness of applications using simple Randomized Completed Block Design (RCBD). Analysis of Varian at 5% level, and Duncan's Multiple Range Test (DMRT) test. Calculations of LC50 and LT50 use probit regression analysis. The results showed that the highest compounds contained in gadung tubers were alkaloids, whereas in grinting grasses were saponins. Both of these compounds have the potential as a base for vegetable insecticides. The combination treatment of gadung extract and grinting 3: 2 (v / v) (P7) and 3: 1 (P8) showed the most effective results compared to positive controls and other treatments with mortality mean values at all observations of 87.44% and 86, 7%. The LC50 value of gadung extract at the first observation was 3%, the grinting extract was 3.08%. The lowest LT50 value is in treatment P7 (3: 2) with a time of 3.88 hours. a combination of gadung extract and grinting can suppress A.glycine infestation and potentially a plant-based insecticide.